Analisis Keterampilan Generik Mahasiswa Melalui Metode Demonstrasi pada Mata Kuliah Pendidikan Lingkungan Hidup - Suci Siti Lathifah; Atik Setiawan (Pedagogia: Jurnal Ilmiah Pendidikan, 2016)
The research is aimed at describing human generic skill through demonstration method in the subject of living environment. It was conducted to 80 students from 2 classes of Primary School Teacher Training Department at the Faculty of Teacher Training and Educational Sciences at Pakuan University. The students’ generic skill was gained through an instrument which was an observational sheet when they did a group activity and was also gained through an individual written test. The research result shows that the students’ generic skill is “adequate. It can be seen from the mean score of the students’ generic skills both in group and also individually (73.06 % and 71.13%). The generic skill which was directly observed in group and individually can be categorized as “good” (78.90% and 74.20%), students’ skill in logical frame both in group and individually was “adequate” (67.23% and 68.56%), students’ skill in knowing cause and effect of a problem in group activity was “adequate” (70.45%) while individually was “good” (77.11%), students’ skill in modeling in group activity was “good” (75,70%) while individually was “adequate” (56.90%), and inference skill of the students in both group and individually was “adequate” (73.06% and 71.13%). Students’ response through the learning activity using demonstration method was positive. The learning using demonstration method is advantageous for the students since it can help them learn living environment. Therefore, it is recommended to apply the method in living environmental education class.